FENOMENA TAWURAN ANTAR WARGA - Sujarwo; Annisa Solikha (Jurnal Ilmiah Mimbar Demokrasi, 2019)
This reseach aims to learn how to deal with conflicts between citizens as social conflicts, and changes that result, and efforts to overcome conflicts between citizens. The reseach was conducted in Kramat Pulo Gundul, Johar Baru, Central Jakarta. This reseach uses qualitative methods to obtain more in-depth data by asking research informants. Techniques for collecting data through involved observation, interviews, use of documents, registration techniques, and field notes. The results of the study concluded, the causes of brawl between residents in Kramat Pulo Gundul were different goals, individual personalities, cultural and defense conflicts, and cultural differences. Fights between residents that occurred in RW 010 Kramat Pulo Gundul, Tanah Tinggi, Johar Baru, Jakarta Damage to public facilities and property, Relationship damage and communication between parties involved in conflict, Negative attitudes and protections, Physical and psychological health, Difficulties looking for work, and lowering the price of houses and land. However, there is a need to worry about reducing the sense of respect and return, peace and life values for each individual.